Bibliometric analysis of tuberculosis molecular epidemiology based on CiteSpace - Zheng, Mei-qin; Li, Xi-xi; Xu, Rui; Liu, Shuo; Rui, Zhi-yong; Guo, Zhen-yong; Chen, Di (Frontiers in Public Health, 2022)
Background: Tuberculosis is a communicable disease that is a major cause of ill health. Bibliometrics is an important statistical methodology used to analyze articles and other publications in the literature study. This paper aims to show a bibliometric overview of publications on the molecular epidemiology of tuberculosis. Methods: The Web of Science database was searched for publications on the molecular epidemiology of tuberculosis with the keywords “tuberculosis” and “molecular epidemiology” in the title. The number of publications, citation analysis, co-authorship of author, institution and country, keyword co-occurrence, and reference co-citations were analyzed. Results: A total of 225 journal articles were retrieved. The mean citation was 37.72 per article and 292.69 per year. The annual publications on molecular epidemiology fluctuated within a certain range in the past. Journal of Clinical Microbiology is the most published journal with 33 articles. RASTOGI N is the most prolific author with 11 articles. The top 1 research institution is Inst Pasteur Guadeloupe. Stratified by the number of publications, the USA was the most prolific country. It also cooperates closely with other countries. The most-cited journal was the New England Journal of Medicine. Burstness analysis of references and keywords showed that the developing research trends in this field mainly focused on “genetic diversity” and “lineage” during the past decade. Conclusion: The annual publications on tuberculosis molecular epidemiology fluctuated within a specific range in the past decade. The USA continues to dominate research output and funding. The exchange of expertise, ideas, and technology is of paramount importance in this field. More frequent and deeper cooperation among countries or institutions is essential in the future.